2012
DOI: 10.1186/1471-2369-13-93
|View full text |Cite
|
Sign up to set email alerts
|

Urinary N-acetyl-β-D glucosaminidase as a surrogate marker for renal function in autosomal dominant polycystic kidney disease: 1 year prospective cohort study

Abstract: BackgroundRenal failure is one of the most serious complications associated with autosomal dominant polycystic kidney disease (ADPKD). To date, early markers have failed to predict renal function deterioration at the early stages. This 1-year prospective study evaluated N-acetyl-β-D-glucosaminidase (NAG) as a new surrogate marker for renal function in ADPKD.MethodsA total of 270 patients were enrolled in the study, and we measured urinary NAG, β2-microglobulin, neutrophil gelatinase-associated lipocalin (NGAL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
2
17
0
2
Order By: Relevance
“…Finally, few studies have investigated the association of urinary NAG with ESRD events, but our study is consistent with prior reports in the Pima Indians and adults with autosomal dominant polycystic kidney disease, where urinary NAG was not associated with CKD progression or eGFR decline after adjustment for traditional risk factors for CKD progression (15,18).…”
Section: Discussionsupporting
confidence: 81%
“…Finally, few studies have investigated the association of urinary NAG with ESRD events, but our study is consistent with prior reports in the Pima Indians and adults with autosomal dominant polycystic kidney disease, where urinary NAG was not associated with CKD progression or eGFR decline after adjustment for traditional risk factors for CKD progression (15,18).…”
Section: Discussionsupporting
confidence: 81%
“…2 Increased urinary NAG activity has been described in various disease states such as heavy metal poisoning and renal diseases. [3][4][5][6][7] Most authors consider increased urinary NAG to be a sensitive marker of tubular injury, 8 related to inflammation and oxidative stress. Albumin in the urine is traditionally considered to be of glomerular origin, 9 although impaired tubular reabsorption may contribute in the pathogenesis of increased urinary albumin excretion (UAE).…”
mentioning
confidence: 99%
“…Interestingly, the urinary NGAL levels in each mouse were correlated with KW. It was also reported that NGAL is abundant in the cyst fluid of patients with ADPKD Park et al, 2012). Therefore, elevated NGAL might be a common feature of PKD in human patients and rodent models.…”
Section: Discussionmentioning
confidence: 99%